Chinese commercial banks’ risk management performance before and after financial crisis: evidence from cost and profit efficiency - Liu, Lian (2012)
This dissertation aims to test whether the financial crisis has adversely affected the Chinese banking system and whether efficiency has effectively materialized in this system using Data Envelop Analysis and Tobit regression model. First, we analyze the trend of overall efficiency for each bank type pre- and post-crisis and compare the different efficiency estimations and the efficiency scores of different bank ownership. Second, we give out several hypotheses regarding the potential determinants of Chinese banking efficiency and the possible relationship between bank efficiency and each determinant. The results are compared to the previous hypotheses and empirical researches. Some arguments are reasonably obtained to explain the results considering the existing circumstances of Chinese banking system.